The Credit Card Debt Puzzle: The Role of Preferences, Credit Access Risk, and Financial Literacy - Gorbachev, Olga; Luengo-Prado, María José (The Review of Economics and Statistics, 2019)
We use the 1979 National Longitudinal Survey of Youth to revisit what is termed the credit card debt puzzle: why consumers simultaneously co-hold high-interest credit card debt and low-interest assets that could be used to pay down this debt. Relative to individuals with no credit card debt but positive liquid assets, borrower-savers have very different perceptions of future credit access risk and use credit cards for precautionary motives. Moreover, changing perceptions about credit access risk are essential for predicting transitions among the two groups. Preferences and the composition of financial portfolios also play a role in these transitions.